Parallel Loop Binding Compression Suture, a Modified Procedure for Pernicious Placenta Previa Complicated With Placenta Increta - Fu, Mengdi; Bu, Hualei; Fang, Yan; Wang, Chunling; Zhang, Li; Zhang, Yang; Sun, Xiao; Li, Mingbao; Jin, Chengjuan; Xu, Yintao; Chen, Lijun (Frontiers in Surgery, 2021)
Objective. To evaluate the efficacy and safety of parallel loop binding suture of the lower uterus during cesarean section in pernicious placenta previa complicated with placenta increta. Methods. This retrospective study was performed in patients with pernicious placenta previa complicated with placenta increta or percreta between November 2014 and December 2020 at the Qilu Hospital of Shandong University. Patients were divided into study group and control group according to whether parallel loop binding compression suture surgery were performed. Postpartum hemorrhage was evaluated as the primary outcome. The secondary outcomes included age, gestational weeks, operative time, fetal childbirth time, prevention of hysterectomy, blood transfusion, duration of postoperative catheterization, duration of antibiotic treatment, and postoperative hospitalization (days). Additionally, neonatal outcomes were evaluated. Results. A total of 124 patients were included in the study, 38 of whom underwent parallel loop binding suture surgery，and 86 patients underwent traditional surgery with suture as the main hemostatic method. With parallel loop binding compression suture, the average operation time was significantly reduced (109.0 ± 33.5 vs. 134.4 ± 54.2 min, p=0.00), and the volume of blood lost were also decreased (2152.6 ± 1169.4 vs. 2960.5 ± 1963.6 ml, p=0.02), which correspondingly reduced RBC transfusion (7.2 ± 3.5 vs. 10.3 ± 8.7 units, p=0.03) and FFP transfusion (552.6 ± 350.3 vs. 968.0 ± 799.8 ml, p=0.00). The fetal childbirth time was extended (14.1 ± 5.6 vs. 11.0 ± 8.0 min, p=0.03), however, there was no increase in NICU admission rates (36.9% vs. 34.9%, p=0.83). Except for one premature infant (32 weeks) death in the control group，all infants at our hospital were safely discharged after treatment. Conclusion. Parallel loop binding compression suture is an effective, swift, practical, and safe method to reduce postpartum bleeding in women with pernicious placenta previa, complicated with placenta increta. Besides, it has no adverse effects on newborns.